Nutritional profile, phytonutrient composition and biocidal properties of Portulaca oleracea L. regarding the ammonium to total nitrogen ratios in hydroponics - Paschoalinotto, Beatriz H.; Chrysargyris, Antonios; Añibarro-Ortega, Mikel; Pires, Tânia C.S.P.; Mandim, Filipa; Dias, Maria Inês; Tzortzakis, Nikos G.; Barros, Lillian (My University, 2025)
The contribution of the ammonium:total nitrogen ratio (Nr0.01–0.15) in the nutrient solution on chemical profile and bioactive characteristics of Portulaca oleracea, investigated. Increased Nr levels resulted in increased proteins, total fats, carbohydrates and oxalic acid in leaves and stems, but decreased yield. The only detected tocopherol isoforms were α- and β-tocopherol, with the former to reveal increased values at Nr0.10. The most abundant sugars found were fructose, glucose, sucrose, and trehalose, while total sugars were positively affected by the increased Nr in stems. The higher Nr ratio had a favourable effect on the fatty acid profile, while Oleracein A was the main phenolic component detected in higher levels at Nr0.05 (leaves) and Nr0.10 (stems). The increased Nr levels increased antimicrobial activity, while antioxidant activity was varied in different Nr levels. The Nr ratio for P. oleracea may stimulate health-promoting components, while reducing antinutrients content, hence improving overall product quality.